Continuous Hydrogeological Characterisation in Iron Ore Deposits Using Borehole Magnetic Resonance. Issue 1 (1st December 2018) - Trofimczyk, Kazimierz; Downey, Mark; Hopper, Tim; Neville, Tom; Birt, Benjamin
Abstract : In situ dewatering of iron ore deposits is essential for safe and efficient mining operations, as well as reducing requirements for subsequent moisture removal for processing and transportation. Evaluating porosity, residual moisture content, and hydraulic conductivity is key to designing effective dewatering schemes. Modern borehole magnetic resonance has been used in the oil and gas industry for over twenty years to provide continuous evaluation of porosity, bound and free fluid volumes, and permeability. As such, it is uniquely suited to provide subsurface characterisation data for dewatering scheme design. However, applying these methods in iron ore settings introduces complications that are not observed in typical oil and gas environments due to the high concentrations of paramagnetic and ferromagnetic iron-containing compounds making up the ores. This requires explicitly accounting for the impact of these compounds on surface and diffusional relaxation when estimating fluid volumes and permeability from magnetic resonance measurements. Development of robust methods for accommodating these effects would allow for practical application of borehole magnetic resonance measurements in iron ore settings, providing continuous and cost effective hydrogeological characterisation.